Degenerative changes in aortic root allografts placed in the right ventricular outflow tract of growing puppies. Issue 6 (December 1976) - Jeong, U G; Khan, A A; Fine, G; Folger, G M; Gonzalez-Lavin, L
Abstract : Differently prepared aortic root allografts were implanted in the right ventricular outflow tract of growing puppies to determine the site of origin and progress of degenerative changes in these conduits. The three preparations assessed were as follows: group A, fresh and sterile grafts; group B, antibiotic sterilized grafts in nutrient medium; and group C, beta-propiolactone sterilized grafts. Although calcification of the aortic wall occurred in all groups, the aortic leaflets were minimally affected. A correlation between viability and lack of calcification and between viability and long-term function is emphasized.